2021
DOI: 10.1111/jdv.17154
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplastic melanoma: a review of its pathology and clinical behaviour, and of management recommendations in published guidelines

Abstract: Desmoplastic melanomas are uncommon. Their behaviour differs from that of other melanoma subtypes; therefore, management guidelines for non-desmoplastic melanomas may not be applicable. This review sought to examine all available evidence relating to the behaviour and management of desmoplastic melanomas, based on review of all relevant English-language publications, and to critically assess the recommendations for their management in current published melanoma management guidelines. Compared with other melano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 59 publications
(196 reference statements)
0
12
0
1
Order By: Relevance
“…A very interesting trial is evaluating neoadjuvant pembrolizumab in patients with resectable stage II or III desmoplastic melanoma (S1512, NCT02775851). Desmoplastic melanoma appears to be particularly sensitive to single‐agent anti‐PD1 immunotherapy 23 and often presents with locally advanced disease due to the fact this variant is frequently amelanotic and lacks the typical recognition features associated with most other primary cutaneous melanoma subtypes 24 . The S1512 trial involved up to three doses of preoperative pembrolizumab before wide excision ± sentinel node biopsy or lymphadenectomy, respectively, for stage II or stage III desmoplastic melanoma.…”
Section: Are There Any Situations Where Neoadjuvant Therapy Should Be...mentioning
confidence: 99%
See 1 more Smart Citation
“…A very interesting trial is evaluating neoadjuvant pembrolizumab in patients with resectable stage II or III desmoplastic melanoma (S1512, NCT02775851). Desmoplastic melanoma appears to be particularly sensitive to single‐agent anti‐PD1 immunotherapy 23 and often presents with locally advanced disease due to the fact this variant is frequently amelanotic and lacks the typical recognition features associated with most other primary cutaneous melanoma subtypes 24 . The S1512 trial involved up to three doses of preoperative pembrolizumab before wide excision ± sentinel node biopsy or lymphadenectomy, respectively, for stage II or stage III desmoplastic melanoma.…”
Section: Are There Any Situations Where Neoadjuvant Therapy Should Be...mentioning
confidence: 99%
“…Desmoplastic melanoma appears to be particularly sensitive to single-agent anti-PD1 immunotherapy 23 and often presents with locally advanced disease due to the fact this variant is frequently amelanotic and lacks the typical recognition features associated with most other primary cutaneous melanoma subtypes. 24 The S1512 trial involved up to three doses of preoperative pembrolizumab before wide excision ± sentinel node biopsy or lymphadenectomy, respectively, for stage II or stage III desmoplastic melanoma. Encouraging preliminary results of this trial were recently presented, 25 and our experience with this approach has indicated that there is a very high rate of pathologic complete response to neoadjuvant pembrolizumab in this melanoma subtype.…”
Section: Are There Any Situations Where Neoadjuvant Therapy Should Be...mentioning
confidence: 99%
“…Desmoplastic melanoma (DM) is regarded as an uncommon form of melanoma that occurs on the head and neck of older people (median age 60–70 years), occurring more often males ( 1 ). Few epidemiological studies of pure DM (≥ 90% uniform desmoplasia) exist, and even fewer have reviewed contemporary DM patients.…”
mentioning
confidence: 99%
“…6,7 However, local recurrences are more frequent because of prevalent perineural spread 5 and often difficult complete excision. 7 Neuropathy has rarely been reported and then mostly in advanced tumour recurrences. 8 In any case, sensory deficits and paresis of peripheral nerves have not been reported as early prodromal signs of DM.…”
mentioning
confidence: 99%
“…6 Desmoplastic melanoma metastasizes less frequently into the lymph nodes 5 and melanoma-specific survival appears to be longer than for other types of melanoma. 6,7 However, local recurrences are more frequent because of prevalent perineural spread 5 and often difficult complete excision. 7 Neuropathy has rarely been reported and then mostly in advanced tumour recurrences.…”
mentioning
confidence: 99%